Heat Transferring Mechanism through Interlacing Structure Using Finite Element Analysis (Journal of Fiber Bioengineering and Informatics, 2018)
Heat transmission in the fabric is strongly related to the thermal comfort, which plays an importantrole when designing fabrics. In this work, a heterogeneous model constructed according to the internalstructure of five woven fabrics was developed to study the heat transmission through fabrics. In thismodel, heat can transfer along the longitudinal and transverse direction of warp and weft yarn at differentrate base on the inputted boundary conditions and constants, such as mass density, specific heat andthermal conductivity. In addition, heat transmission occurring in the contacting interface between thewarp and weft yarn was also considered. The validity of this model was then confirmed by the highconsistency between the thermal resistance obtained from experiment and simulation. The simulationresults suggested that heat mainly transfers inside the same yarn, with only a very small portion of heatexchange between the warp and weft yarn via their contacting region. Besides, the calculated fabricthermal resistance is obviously affected by the size of contacting area between fabric and heat source.
Keywords: 3D heterogeneous model; Heat transfer; Textile; Heat flow